A 1.85 Ga volcanic arc offshore the proto-continent Fennoscandia in southern Sweden - Salin E.; Sundblad K.; Lahaye Y. (Elsevier B.V., 2022)
The Fröderyd Group forms part of the Vetlanda-Oskarshamn belt (also known as the Oskarshamn-Jönköping Belt), which is a piece of Palaeoproterozoic crust that is completely encapsulated by 1.81–1.77 Ga granitoids of the Transscandinavian Igneous Belt in the southern part of the Fennoscandian Shield. New U-Pb zircon data from a felsic metavolcanic rock in the Fröderyd Group have been acquired using LA-ICP-MS single collector. The age is determined to 1853 ± 11 Ma. The Fröderyd Group is interpreted to represent a volcanic arc that was located southwest of the margin to the proto-continent Fennoscandia. Tonalitic magma, identified in the Eksjö-Bäckaby regions, formed the middle crust in this arc complex and intruded the volcanic arc rocks at ca. 1.83–1.82 Ga. When this arc complex gradually approached the margin to the proto-continent Fennoscandia, parts of it were uplifted above sea level and initiated lacustrine sedimentation in restricted basins, which now are found in the Vetlanda region. Parallel with the development of this arc complex, 1.86–1.85 Ga granitoids intruded the margin to the proto-continent Fennoscandia and 1.87–1.86 Ga clastic metasedimentary rocks in the Västervik area in an Andean-type active continental margin.
It can be concluded that the Vetlanda and Västervik sedimentary basins formed in two completely different geological environments during two separate events. The Västervik sediments formed along the margin to the proto-continent Fennoscandia before the Fröderyd arc system had developed while the Vetlanda sediments formed in a post-arc environment outboard to the southwest of the margin to the proto-continent Fennoscandia. It is suggested that the mafic volcanic rocks close to the lake Nömmen should be excluded from the Vetlanda supergroup and instead be related in time to the Fröderyd Group. This paper presents an interpretation of the tectonic evolution including volcanic arc and rifted volcanic arc during the 1.87 to 1.77 Ga time span with relevance to the evolution of the active southwestern margin of the proto-continent Fennoscandia depicted as a sequence of schematic profiles.